Pengaturan Pendaftaran Secara Online Single Submission terhadap Usaha Kecil dan Menengah di Indonesia - Zaini Munawir; Sri Hidayani (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The OSS system is aimed at accelerating and increasing investment and making efforts and making it easier for Business Actors, both individuals, and non-individuals. To simplify the registration/management of business activity licenses, for example, the purpose of this study is to determine the background of OSS registration for MSMEs in Indonesia and its implementation in Indonesia. This research is normative legal research. Normative legal research is research that discusses legal aspects, by conducting library research that is oriented towards applicable laws and regulations. Registration is the registration of businesses and/or activities by Business Actors through OSS. Business Actors as referred to in Article 6 of Government Regulation Number 24 of 2018 shall register for business activities by accessing the OSS page as stipulated in Government Regulation Number 24 of 2018 concerning Electronically Integrated Business Licensing Services.